Efficiency of use of supplementary lighting in rearing of dairy calves during milk feeding stage - Gledson L. P. de Almeida; Héliton Pandorfi; Fátima Baptista; Cristiane Guiselini; Vasco F. da Cruz; Gleidiana A. P. de Almeida (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACTThe objective of this study was to evaluate programs of supplementary lighting for calves in individual shelters with different roof materials, as a strategy to stimulate concentrate consumption and the reduction of the milk feeding period and increase financial viability. Twenty seven dairy crossed Holstein × Gir female calves were randomly distributed in individual shelters with three different roofing materials (cement fiber tile, recycled tile and thatched roofs), associated with three different light duration (12, 16 and 20 h) and with three repetitions. The experimental design was completely randomized in 3 × 3 factorial arrangement. There was no interaction between the types of roofs × supplemental light; also, there was no significant effect of the covering types on the average consumption of concentrate and occurance of diarrhea in calves. On the other hand 20 h of lighting stimulated the consumption of concentrate and allowed weaning of calves at 55 days of age and 20% reduction in the cost of rearing animals during milk feeding stage.